IS Resilience in Southeast Asia? - Singh, Jasminder (2020)
Despite the death of IS’ “caliph” Abu Bakr al-Baghdadi in October 2019, events in Southeast Asia have since shown that IS networks, while weakened through the loss of key leaders and fighters, have regrouped and continued attempts to launch attacks.